Challenges of welfare-to-work programs. - Precin PJ; Precin P (Work, 2011)
Governmental expectations of placement outcomes were often high given the severity of work barriers that were present in disabled welfare recipients in the United States [11]. The purpose of this article is to identify challenges that were inherent in welfare-to-work programs and solutions to these challenges. Although rich with opportunity, welfare-to-work programs presented the challenge of employing large numbers of difficult-to-employ individuals before their public assistance benefits expired\cite{5}. Many clients also had symptoms of Posttraumatic Stress Disorder (PTSD) secondary to childhood physical or sexual abuse (59%) or severe domestic violence (55%) [8]. Few funds were available for work training and education. Instead, the employment-first model was expected even though most consumers did not have a high school diploma, had not worked in years, and were fearful and resistant about returning to work [3]. Performance based payment systems presented a challenge because the program's future depended on the compliance of its consumers. There was an impetus for substance abusers to return to work even if they were still using drugs, which contradicted the teachings of many recovery models. This paper presents possible solutions to each of these problems and reports outcomes of one particular welfare-to-work program. By examining the challenges of welfare-to-work programs, by identifying solutions, and by realizing that these solutions are inherent in the basic principles of rehabilitation, this article provides therapists with tools and motivation to make unique contributions to this area of practice.